ORIGINS OF A MISTRUST: THE CHILEAN COMMUNIST PARTY FACES THE NATIONALIST REVOLUTIONARY MOVEMENT AND THE DICTATORSHIP OF VILLARROEL IN BOLIVIA (1943-1946) - Fernández Abara, Joaquín (Revista de Historia Social y de las Mentalidades, 2024)
The article discusses the interpretation of the  Chilean Communist Party on the Dictatorship of  Gualberto Villarroel in Bolivia and performance  that had in it the Revolutionary Nationalist  Movement, between 1943 and 1946. The author  argues that this interpretation was marked by  anti-fascism and an interpretation of Bolivian  history influenced by liberal platitudes. Thus,  nationalism MNR and the Bolivian military was  depicted as a form of fascism and his role in the  Latin American context was analyzed under a  panamerican perspective, considering it as part of  a plan of the Axis to hinder the work of the Allies  in America. In this line, the Chilean Communists  fought for the Chilean Foreign Ministry denied  recognition to the Bolivian government and  entered into conflict with political and union  actors prone to recognition of the Bolivian  Dictatorship.
Keywords: Chilean Communist Party; Bolivia; Antifascism; Nationalist Revolutionary Movement; Gualberto Villarroel